Searching for R-process-enhanced Stars in the LAMOST Survey. II. Two New r-II Stars in the Milky Way Disk - Xiao-Jin Xie; Jianrong Shi; Hong-Liang Yan; Tian-Yi Chen; Carlos Allende Prieto; Timothy C. Beers; Shi-Lun Jin; Shuai Liu; Chun-Qian Li; Ze-Ming Zhou; Ming-Yi Ding; Yao-Jia Tang (The Astrophysical Journal)
R -process-enhanced (RPE) stars are rare and typically metal-poor ([Fe/H]  < −1.0), primarily found in the Milky Way halo system and dwarf galaxies. This study reports the discovery of two relatively bright, highly RPE stars ([Eu/Fe]  >  +0.70) located in the Milky Way disk, with [Fe/H] of −0.34 and −0.80, respectively. These two stars are selected from the Large Sky Area Multi-Object Fiber Spectroscopic Telescope medium-resolution ( R  ∼ 7500) spectroscopic survey. Follow-up high-resolution ( R  ∼ 25,000) observations were conducted with the High Optical Resolution Spectrograph installed on the 10.4 m Gran Telescopio Canarias. We perform the determination of elemental abundances and calculate the orbital parameters. We find that they are r -II stars with elemental abundances in agreement with the solar r -process pattern. These two objects are chemically and dynamically consistent with membership in the Galactic disk and exhibit no evidence of being part of accreted systems.